Application of Electrical Conductivity (EC) for Some Potato Varieties in the Aeroponically Seed Production with Root Zone Cooling and Evaporative Cooling in Tropical Lowlands - Eni Sumarni; Priswanto Priswanto; Zaroh Irayani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
Aeroponic potato seed production in the lowlands has been carried out by root zone cooling and evaporative cooling in order to reduce high temperature stress for the roots and tops of potato plants. However, the effect of nutrient solution EC on several varieties of potato seeds for an aeroponic system with a combination of root zone cooling and evaporative cooling for potato seed production in the lowlands has not been done. This study aims to obtain the response of potato varieties and the application of different ECs on aeroponic seed production with root zone and evaporative cooling in tropical lowlands. The factors analyzed : 1. Variety (V): V1 (MZ), V2 (Granola K), V3 (Granola L), and 2. Nutrient concentration (EC): EC1 (1.5 mS/cm for Week 1- 4, 2 mS/cm for Week 5 until harvest), and EC2 (1.5 mS/cm for Week 1-4, and 3 mS/cm for Week 5 until harvest), while the design used was RAK with 3 replications. The results showed that the Granola K and EC2 varieties are more efficient for potato seed production in the lowlands with the application of root zone and evaporative cooling. This variety produced the highest number of tubers up to 30 tubers/plant. Similarly, the Granola L and MZ varieties showed similar results with a total number of tubers above 10 tubers/plant. Keywords: Cultivation, Greenhouse, Hydroponics,  Nutrition,  Tubers